Estudo reológico de emulsões água em óleo de petróleos pesados - Coelho Neto, Dorval Moreira (2017)
Unconventional oils (heavy and extra-heavy oils) make up about 55% of the world's oil reserves. The high viscosity and density makes the viable production of these oils challenging. Population growth, coupled with modern living habits, implies a greater demand for energy sources, indicating a possible need for greater exploitation of unconventional oils. The heavy oils are characterized by the high amount of resins and asphaltenes, natural emulsifiers that combine the presence of water and shear, in the stages of production and transportation of oil, provide the formation of emulsions, usually water in oil (W/O). The present study evaluated the rheological behavior of W/O emulsions of five heavy oils from the sedimentary basin of the Brazilian coast, with API gravity between 10.8 and 19.9. Factors related to stability (temperature, amount of emulsified water, salt concentration) and rheological behavior of the W/O emulsions (dynamic viscosity, stress and shear rate) were evaluated. These factors were related to the chemical composition of petroleum in terms of saturates, aromatics, resins and asphaltenes (SARA). The emulsions were prepared with deionized water, formation water (55·103mg·L-1of NaCl) and water saturatedwith sodium chloride (270·103mg·L-1of NaCl) under mechanical stirring at 5000 rotations per minute (rpm). Rheological tests of the emulsions were performed at 30 to 80ºC and the data obtained were treated using the Oswald-de-Waele equation. The results of the rheological evaluation showed that in the stable emulsions, those in which no emulsified water after shearing was identified, there was up to 1212% increase in the dynamic viscosity caused by the increase of the aqueous phase and the influence of the salt concentration. The increase intemperature minimized this effect, and at 60ºC a reduction of more than 80% was observed in the dynamic viscosity of these emulsions. In the stable emulsions, the flow index was positive, showing reduction as a function of the increase of the amount of emulsified water, but inversely related to temperature. For the unstable emulsions, characterized by the presence of non-emulsified water, in the unstable emulsions the dynamic viscosity was lower than the dehydrated oils, and most of them with a negative flow index. In most unstable emulsions, the elevation of salt concentration and temperature aided in the stabilization of the emulsions. It was observed that oils with total acid number less than 1.3 mgKOH·g-1and asphaltene/resin, aromatic/saturated and asphaltene/aromatic ratios higher than 0.2 formed unstable emulsions, resulting in appearance of water Not emulsified during the rheological tests.